2016
DOI: 10.1080/10942912.2016.1172086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of juice concentration on storage stability, betacyanin degradation kinetics, and sensory acceptance of red-fleshed dragon fruit (Hylocereus polyrhizus) juice

Abstract: The aim of this study was to evaluate the effect of red-fleshed dragon fruit (Hylocereus polyrhizus) juice concentration on betacyanin degradation kinetics and sensory acceptance. The samples stored at 4°C were comparatively stable compared to 25°C in terms of betacyanin retention, and yeast and mold growth. The loss of betacyanin in red-fleshed dragon fruit juice and concentrate at 25, 37, and 45°C were of firstorder reaction. The drink reconstituted from red-fleshed dragon fruit concentrate showed better acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…The significantly low score recorded in 1:4 dilution sample could be due to the bland taste after diluted 5 times with water. The findings were in accordance with results reported in a study done by Siow and Wong [20]. The study showed that panelists preferred sweeter drink reconstituted from red dragon fruit concentrate compared to fresh, grassy-smell like red dragon fruit juice.…”
Section: Hedonic Testsupporting
confidence: 92%
See 3 more Smart Citations
“…The significantly low score recorded in 1:4 dilution sample could be due to the bland taste after diluted 5 times with water. The findings were in accordance with results reported in a study done by Siow and Wong [20]. The study showed that panelists preferred sweeter drink reconstituted from red dragon fruit concentrate compared to fresh, grassy-smell like red dragon fruit juice.…”
Section: Hedonic Testsupporting
confidence: 92%
“…In addition, quantification of betacyanin content using spectrophotometer might lead to overestimation of betanin content in the sample due to different types of betacyanin that present in red dragon fruit [23]. Therefore, direct comparison of results in the study done by Siow and Wong [20] with present study was not suitable. Table 1 showed that there was no significant effect of storage temperatures and duration on water activity of FRDFD.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…[17] Hence, different concentrations of roasted salt were included in the formulations in addition to cumin and cardamom. Evaluation of the sensory properties of the food samples was commonly practised after changing the ingredients [18,19] in order to check their acceptability. Here, responses from 100 panellists were obtained and consolidated to get the summary of sensory scores for the quality attributes of kokum samples (Table 2) and that of quality attributes of kokum juice samples in general (Table 3).…”
Section: Resultsmentioning
confidence: 99%